2007
DOI: 10.37833/cord.v23i2.167
|View full text |Cite
|
Sign up to set email alerts
|

Integrated management of Eriophyid mite, Aceria guerreronis Keifer on coconut in Tamil Nadu, India

Abstract: A field experiment was conducted at Vellalore from January 2002 to December 2004 to evaluate the influence of organic and inorganic nutrients and the effect of botanicals and insecticide against coconut eriophyid mite. Soil application of nutrients along with spraying of Triazophos 40 EC (5 ml/lit.), azadirachtin 1% (5 ml/lit.) and neem oil (30 ml/lit.) as first, second and third round of sprayings, respectively were evaluated. The results revealed that there was a significant reduction in mite population (65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 1 publication
0
19
1
2
Order By: Relevance
“…The spikelets from different bunches touch each other naturally as a result of wind action and the bending of the structure with the increased weight of the fruits. Some authors (Galvão et al, 2012;Moore and Alexander, 1987;Sumangala and Haq, 2005) have reported that the pathway of A. guerreronis through the spikelets is a relevant process in the infestation of new bunches. However, as evaluated by the present study, the removal of the spikelets had no significant effect on the damage level of newly produced bunches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spikelets from different bunches touch each other naturally as a result of wind action and the bending of the structure with the increased weight of the fruits. Some authors (Galvão et al, 2012;Moore and Alexander, 1987;Sumangala and Haq, 2005) have reported that the pathway of A. guerreronis through the spikelets is a relevant process in the infestation of new bunches. However, as evaluated by the present study, the removal of the spikelets had no significant effect on the damage level of newly produced bunches.…”
Section: Discussionmentioning
confidence: 99%
“…The coconut mite [Aceria guerreronis Keifer (Acari: Eriophyidae)] is a serious pest of coconuts in the Americas and Africa, and it has rapidly become established in some major coconut-producing countries in Asia (Lawson-Balagbo et al, 2008;Moore and Howard, 1996;Ramaraju et al, 2002). The mite damages the fruit during the early developmental stages, causing surface scars and premature fruit fall (Moore and Howard, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems possible that many coconut varieties grown earlier in India were tolerant to the coconut mite (Haq et al, 2002). Studies on varietal purification have been conducted by several authors in the past (Grinwood, 1975;Thampan, 1984;Ramaraju et al, 2002) with regard to general crop improvement and disease resistance, but specific attention to varieties showing less or no susceptibility to the coconut mite has been dedicated only recently in India. Considering the extensive variation of coconut plants in this country, comprehensive studies to determine varieties resistant to the coconut mite are warranted.…”
Section: Varietal Differences In Susceptibilitymentioning
confidence: 99%
“…Attempts to develop hybrids resistant to this pest have been initiated. Several hybrids, namely Laccadive Ordinary (LO), Cochin China (CC), Andaman Ordinary (AO), Gangabandan (GB) (Muthiah & Bhaskaran, 1999), Kenthali, Tiptur tall, Saint Vincent ECT, WCT, WCTxCOD (Ramaraju et al, 2002;Kannaiyan et al, 2002), have been identified as promising. Among these, GB x WCT and ECT x GB have shown the lowest levels of susceptibility.…”
Section: Varietal Differences In Susceptibilitymentioning
confidence: 99%